Mirror therapy for patients with severe arm paresis after stroke – a randomized controlled trial. (April 2013) - Thieme, Holm; Bayn, Maria; Wurg, Marco; Zange, Christian; Pohl, Marcus; Behrens, Johann
Objective: To evaluate the effects of individual or group mirror therapy on sensorimotor function, activities of daily living, quality of life and visuospatial neglect in patients with a severe arm paresis after stroke. Design: Randomized controlled trial. Setting: Inpatient rehabilitation centre. Subject: Sixty patients with a severe paresis of the arm within three months after stroke. Interventions: Three groups: (1) individual mirror therapy, (2) group mirror therapy and (3) control intervention with restricted view on the affected arm. Main measures: Motor function on impairment (Fugl-Meyer Test) and activity level (Action Research Arm Test), independence in activities of daily living (Barthel Index), quality of life (Stroke Impact Scale) and visuospatial neglect (Star Cancellation Test). Results: After five weeks, no significant group differences for motor function were found ( P > 0.05). Pre–post differences for the Action Research Arm Test and Fugl-Meyer Test: individual mirror therapy: 3.4 (7.1) and 3.2 (3.8), group mirror therapy: 1.1 (3.1) and 5.1 (10.0) and control therapy: 2.8 (6.7) and 5.2 (8.7). However, a significant effect on visuospatial neglect for patients in the individual mirror therapy compared to control group could be shown ( P < 0.01). Furthermore, it was possible to integrate a mirror therapy group intervention for severely affected patients after stroke. Conclusion: This study showed no effect on sensorimotor function of the arm, activities of daily living and quality of life of mirror therapy compared to a control intervention after stroke. However, a positive effect on visuospatial neglect was indicated.